Polarization reversal of Bulk Ferroelectrics - Mohamad Nazri, Abdul Halif; Junaidah, Osman (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.